FORMULATION AND EVALUATION OF PH-DEPENDENT COLON-TARGETED TABLETS OF RIFAXIMIN BY DESIGN OF EXPERIMENT - RAWOOF MD; RAJNARAYANA K; AJITHA M (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The research is designed at formulating and evaluating pH-sensitive rifaximin colon-targeted tablets for targeted action in proximal colon. Method: The colon-targeted tablets are done by granulation of three levels of polymers such as Eudragit L30D, Carbopol 974P, and ethyl cellulose. The evaluation parameters such as swelling studies, drug dissolution, in vitro drug release studies, stability, and the Fourier transform infrared studies carried out for optimized formulations. Results: Physicochemical parameters of all the 27 formulations (RF1-RF27) evaluated and RF21 is chosen for further investigation based on weight variation, hardness, drug content, and swelling index. The in vitro drug release studies indicate that the optimized formulation RF21 released 98.75% drug within 24 h. The stability studies indicate that the formulation is stable. Conclusion: An effective and stable pH-dependent rifaximin colon-targeted tablet formulated for the targeted treatment of bowel syndrome.